Bài giải
a, \(\left|x+3\right|+\left|y-1\right|=0\)
Mà \(\hept{\begin{cases}\left|x+3\right|\ge0\forall x\\\left|y-1\right|\ge0\forall x\end{cases}}\Rightarrow\hept{\begin{cases}\left|x+3\right|=0\\\left|y-1\right|=0\end{cases}}\Rightarrow\hept{\begin{cases}x=-3\\y=1\end{cases}}\)
Vậy \(\left(x\text{ ; }y\right)=\left(-3\text{ ; }1\right)\)
b, \(\left|x+5\right|+\left|y+1\right|\le0\)
Mà \(\hept{\begin{cases}\left|x+5\right|\ge0\forall x\\\left|y+1\right|\ge0\end{cases}}\Rightarrow\text{ }\left|x+5\right|+\left|y+1\right|=0\)
Dấu " = " xảy ra khi \(\hept{\begin{cases}\left|x+5\right|=0\\\left|y+1\right|=0\end{cases}}\Rightarrow\hept{\begin{cases}x=-5\\y=-1\end{cases}}\)
Vậy \(\left(x\text{ ; }y\right)=\left(-5\text{ ; }-1\right)\)